The Use of Spatial Econometrics, Stakeholder Analysis and Qualitative Methodologies in The Evaluation of Rural Development Policy - Yang, A.L.; Rounsevell, Mark D.; Haggett, C.; Piorr, A.; Wilson, R.M. (World Scientific Publishing, 2015)
The analysis and evaluation of European Rural Development Policy (RDP) is challenging because of its delivery at multiple scales by multiple actors. To address this challenge the Common Monitoring and Evaluation Framework (CMEF) indicators were introduced. However, these quantitative indicators are limited by data gaps and their inability to address the less tangible aspects of policy performance. In this paper we explore, how to address these limitations through complimentary policy evaluation approaches using evidence from empirical studies. We discuss the strengths and weakness of applying three different quantitative and qualitative evaluation approaches: (1) spatial econometrics; (2) stakeholder analysis; and, (3) qualitative interviews. The findings from the three methods are then triangulated proposing the potential of an integrated methodological approach to inform policy and management. A mixed method approach provides a broader understanding of how policy design, stakeholder's roles, and spatial characteristics impact on implementation and environmental targeting capacity, highlighting the multifaceted nature of the determinants of policy performance.